Profiling ISIS Supporters on Twitter - Gomes, Bruno Guilherme; Holanda, Pedro H. F.; Silva, Ana Paula Couto da; Goussevskaia, Olga (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2017: Proceedings of the 23rd Brazilian Symposium on Multimedia and the Web, 2017)
Cyber Terrorism is a real threat to the modern society. Many terrorist organizations spread their ideas and recruit new supporters over Online Social Networks. Among all terrorist organizations, ISIS can be considered as the biggest one, which is responsible for inspiring terrorist actions in more than 20 countries. As expected, ISIS uses Twitter for spreading its hatred, and an important issue is how to characterize these supporters in order to understand their motivation. Our work investigates and discusses the way ISIS organizes within Twitter. We base our analyses on two curated datasets. The first dataset, “How ISIS Uses Twitter” (HIUT), is provided by the Fifth Tribe digital agency. The second dataset, “Syria and ISIS Mentioners” (SIM), we collected ourselves and curated without participation of experts in the field. We made the SIM dataset publically available, helping new studies in the understanding of ISIS supporters’ profiles on Twitter. The main contribution of this work is a characterization of both HIUT and SIM datasets.